Identification of an ergosterol derivative with anti-melanoma effect from the sponge-derived fungus Pestalotiopsis sp. XWS03F09 - Xia, Tong; Lei, Hui; Wang, Jianv; He, Yijing; Wang, Hailan; Gao, Lanyang; Qi, Tingting; Xiong, Xia; Liu, Li; Zhu, Yongxia (Frontiers in Microbiology, 2022)
It is difficult to treat malignant melanoma because of its high malignancy. New and effective therapies for treating malignant melanoma are urgently needed. Ergosterols are known for specific biological activities and have received widespread attention in cancer therapy. Here, LH-1, a kind of ergosterol from the secondary metabolites of the marine fungus Pestalotiopsis sp., was extracted, isolated, purified, and further investigated the biological activities against melanoma. In vitro experiments, the anti-proliferation effect on tumor cells was detected by MTT and colony formation assay, and the anti-metastatic effect on tumor cells was investigated by wound healing assay and transwell assay. Subcutaneous xenograft models, histopathology, and immunohistochemistry have been used to verify the anti-tumor, toxic, and side effect in vivo. Besides, the anti-tumor mechanism of LH-1 was studied by mRNA sequencing. In vitro, LH-1 could inhibit the proliferation and migration of melanoma cells A375 and B16-F10 in a dose-dependent manner and promote tumor cell apoptosis through the mitochondrial apoptosis pathway. In vivo assays conﬁrmed that LH-1 could suppress melanoma growth by inducing cell apoptosis and reducing cell proliferation, and it did not have any notable toxic effects on normal tissues. LH-1 may play an anti-melanoma role by up-regulating OBSCN gene expression. These findings suggest that LH-1 may be a potential for the treatment of melanoma.